Chronic bullous disease of childhood. - Wojnarowska, F (1988)
Chronic bullous disease of childhood is a well defined clinical and immunopathological entity that is probably the childhood counterpart of adult linear IgA disease. The dogma of universal remission before puberty is not true and unsuspected ocular scarring may occur, so the prognosis should be guarded. Understanding of this disease is rapidly evolving and we are near identification of the antigen, but we do not know why the disease is IgA mediated, nor the initial trigger for the autoimmune response.